2014
DOI: 10.1098/rstb.2013.0341
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary and future studies in plant speciation, morphological/floral evolution and polyploidy: honouring the scientific contributions of Leslie D. Gottlieb to plant evolutionary biology

Abstract: One contribution of 14 to a Theme Issue 'Contemporary and future studies in plant speciation, morphological/floral evolution and polyploidy: honouring the scientific contributions of Leslie D. Gottlieb to plant evolutionary biology'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 143 publications
(224 reference statements)
0
4
0
Order By: Relevance
“…First, it was reported that ancient whole‐genome duplications (WGDs) successfully survived because they occurred at specific times during major ecological upheavals and periods of extinction (Peer et al ., ). For instance, the ancient burst of genome duplications occurred close to the Cretaceous–Tertiary (K–T) boundary, when most living organisms went extinct (Peer et al ., ; Crawford et al ., ), and the present‐day polyploidy in the Arctic which is one of Earth's most polyploidy‐rich areas (Brochmann et al ., ). Second, many studies on allopolyploids have found that although genome duplication has less effect on gene expression change, it has a greater influence on stress response (Hegarty and Hiscock, ; Church and Spaulding, ; Jackson and Chen, ; Parisod et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…First, it was reported that ancient whole‐genome duplications (WGDs) successfully survived because they occurred at specific times during major ecological upheavals and periods of extinction (Peer et al ., ). For instance, the ancient burst of genome duplications occurred close to the Cretaceous–Tertiary (K–T) boundary, when most living organisms went extinct (Peer et al ., ; Crawford et al ., ), and the present‐day polyploidy in the Arctic which is one of Earth's most polyploidy‐rich areas (Brochmann et al ., ). Second, many studies on allopolyploids have found that although genome duplication has less effect on gene expression change, it has a greater influence on stress response (Hegarty and Hiscock, ; Church and Spaulding, ; Jackson and Chen, ; Parisod et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Crosses among taxa of different ploidal levels may lead to hexaploids and other higher level polyploids. Given the potential for polyploids of various natures to have different evolutionary outcomes (Otto and Whitton, 2000; Doyle et al, 2008; Hegarty and Hiscock, 2008; Soltis et al, 2010; Arrigo and Barker, 2012; Buggs et al, 2014; Crawford et al, 2014; Garsmeur et al, 2014; Barker et al, 2016), a better characterization of paleopolyploidies is an important next step in understanding the evolution of plant genomes.…”
mentioning
confidence: 99%
“…This result, recently substantiated in a survey of 13 additional taxa (Baack et al, 2015), lends further weight to arguments for the importance of early‐acting barriers. However, the diversity of the plant kingdom virtually guarantees that the path to speciation is not uniform across taxa, and identifying predictable elements of the speciation process continues to be a challenge (Stebbins, 1950; Grant, 1981; Rieseberg and Willis, 2007; Crawford et al, 2014).…”
mentioning
confidence: 99%